The MIDA quantitative international registry: prognostic implications of moderately elevated pulmonary artery pressure. (4th February 2022) - Essayagh, B; Benfari, G; Antoine, C; Grigioni, F; Le Tourneau, T; Roussel, JC; Ajmone, N; Van Wijngaarden, A; Delgado, V; Bax, J; Tribouilloy, C; Hochstadt, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background:   Pulmonary hypertension is a frequent complication of severe degenerative mitral regurgitation (DMR) associated with major outcome implications. However, whether pulmonary hypertension is linked with worse outcome in less that severe MR is uncertain and even more unsubstantiated is the link of elevated systolic pulmonary artery pressure (sPAP) < 50mmHg with clinical presentation and outcome. Purpose: To assess the outcome implication of sPAP elevation, even moderate, among mitral regurgitation severity subgroups. Methods: The MIDA-Quantitative (MIDA-Q) unprecedented registries included 7373 consecutive patients (age 64 ± 17 years, 45% women, follow-up 5.5 ± 3.4 years) with isolated DMR diagnosed at tertiary (European/North-American/Middle East) centers in which systolic pulmonary artery pressure (sPAP) was measured prospectively at baseline. Long-term survival overall, under medical management and post-mitral surgery was analyzed. Results:  Elevated pulmonary pressure (sPAP >50mmHg) was observed in 1371 patients (19%, mean 63 ± 13mmHg) and moderate increase in pulmonary pressure (35< sPAP < 50mmHg) in 1874 patients (25%, mean 41 ± 14mmHg), with no/mild MR in 4067 (50%), moderate in 2073 (25%), and severe or above in 2047 (25%), mean ERO 0.24 ± 24cm2, RVol 37 ± 35mL and posterior leaflet prolapse in 34%. sPAP severe but also moderate both strongly and independently linked to more severe clinical presentation, with more dyspnea, more AFib, and impaired renal function (P ≤ 0.0001). By sPAP categories,   35 < sPAP< 50mmHg (vs. 35mmHg) was independently associated with worse outcome under medical management adjusted-HR 1.62[1.40-1/87], with considerable excess-mortality for sPAP > 50mmHg (vs. <35mmHg) adjusted-HR 2.54[2.17-2.96], all P < 0.0001. As continuous variable, sPAP was associated with worse outcome adjusted-HR 1.25[1.21-1.29], P < 0.0001 per 10mmHg-increase. Mitral valve surgery (performed in 2378 patients, 32%) improved outcome without alleviating completely higher mortality associated with sPAP > 50mmHg (P < 0.0001). Conclusion: In this very large international cohort of patients with DMR of all range and prospective sPAP grading, higher sPAP is associated at diagnosis with more severe clinical presentation. Long term, sPAP > 50mmHg but also 35-50mmHg is independently of all confounders, associated with worse mortality. Thus careful assessment and consideration for mitral surgery/transcatheter therapy is warranted even in patients with sPAP <50mmHg.